Fabrication of an optical fiber reflective notch coupler. - Rushworth, C; James, D; Jones, C; Vallance, C (2011)
A method of fabricating a reflective notch coupler in an optical fiber has been developed. The coupler consists of a 45° microprism that penetrates into the core of a multimode optical fiber. One face, at 90° to the fiber axis, is nonreflective, and one face, at 45° to the fiber axis, is reflective. Our method of fabricating a notch and selectively mirroring only the 45° face is low-cost, precise, and easily scalable. The coupler allows near-100% coupling of light into an optical fiber from the side, while allowing coupling of any desired fraction of light out from the core at a 90° angle on the opposite side of the fiber.